TENDENCY TO WATCH INDIAN TV SERIALS OF STUDENTS: A STUDY ON KHULNA UNIVERSITY - Tarannum, Nishat; Siddiqa, Aisha (South Asian Journal of Social Sciences and Humanities, 2024)
This study investigates the influence of Indian TV serials on the lifestyles of female students of Khulna University. This study was executed by using qualitative method of research. It targeted 100 female respondents aged 18-25 years from Khulna university students who were selected through purposive sampling method. Researcher used the Uses and gratifications theory, cultivation theory and social learning theory. This study also recorded the respondent’s favorite Indian TV channels, preferred serials and category, favorite watching time, communication pattern and understanding level, level of viewing etc. The general findings reveal that, Indian TV serials have significant influence on the lifestyles of the female students. Alongside, these Indian TV serials impose the indigenous culture, fashion, art, tradition, rituals, language and customs in every sphere of life due to heavy dependency on Indian TV serials. They are constantly becoming more and more addicted to Indian TV serials and giving less importance to other educational or entertainment programs whereas they are giving more priority to these serials. In fact, the analysis shows that majority of female students are jeopardized in their studies due to watching Indian TV serials. Today’s young generation is instinctively influencing by Indian norms culture and tradition which is a big threat for Bangladeshi culture as well. This research study demonstrates how Indian TV serials are influencing female’s lifestyles.